OBTAINING EXTERNAL CYLINDRICAL SURFACES USING A TOOL ELECTRODE TYPE PLATE WITH HOLES (Nonconventional Technologies Review, 2017)
External cylindrical surfaces could be obtained in workpieces made of electro conductive materials both by classical machining methods and nonconventional machining methods. One of such nonconventional machining methods is the electrical discharge machining method. If it is necessary to obtain small diameter external cylindrical surfaces, a method based on the use of a plate type tool electrode with holes of adequate diameters could be applied. Practically, as a consequence of the common linear work movement, the workpiece material is gradually removed and only the material corresponding to the hole is not affected by the process of material removal, constituting gradually a cylindrical column. The theoretical analysis of the process developed in such conditions showed that various factors could affect the depth of tool electrode penetration into the test piece material. Experimental researches aiming to highlight the influence exerted by some process input factors (pulse on time, pulse off time, peak current intensity, and process duration) on the height of columns generated by electrical discharge machining were designed and materialized. By mathematical processing of the experimental results, empirical mathematical models were determined. These models showed that the penetration depth increases when the peak current intensity and process duration increase and diminishes when the pulse on time and pulse off time increase.
Keywords: electrical discharge machining; external cylindrical surfaces; plate type electrode; experimental research; empirical mathematical models.